Tuberculosis with new onset of diabetes and hypertension following recovery from coronavirus disease 2019 infection: A case series - Rupak Chatterjee; Aitihya Chakraborty; Kumkum Sarkar; Netai Pramanik; Shatavisa Mukherjee (Journal of the Practice of Cardiovascular Sciences, 2023)
The sign and symptoms of coronavirus disease 2019 (COVID-19) and infectious disease caused by severe acute respiratory syndrome coronavirus 2 are not only restricted to the respiratory system but includes a myriad of clinical manifestations involving various systems. There are various sequelae of COVID-19 reported. Here, we report a series of three cases of tuberculosis along with new onset of diabetes mellitus and hypertension in previously euglycemic, normotensive patients following recovery from COVID-19.